New Wine In Old Bottles: Revitalizing The Traditional History Lecture - Blackey, Robert (Teaching History: A Journal of Methods, 1997)
Active learning. … student-centered learning …. interactive learning …. collaborative education …. student-directed learning.… empowerment in the classroom. The jargon of cognitive psychology and education makes many historians cringe. While there doubtless are good educational techniques and substance lurking behind these terms, an underlying premise is that the traditional lecture1 does not work, that by its very nature lecturing renders students passive learners, induces apathy, and runs a greater risk of boring them into not learning at all (e.g., much of the content presented via lecture "is not attended to by students and what is attended to may be distorted on its path from the lecturer's notes to the students"2). Although it is certainly possible that lecturing can contribute to a student's failure to learn, the contention here is that such results are not inevitable, that lecturing, especially history lecturing, can be made to promote learning in a way comparable to any other technique. I myself learned a great deal-certainly more than just historical facts and dead-weight information-from several outstanding lecturers. And I have gotten enough feedback over more than a quarter century of teaching to believe that I have had at least some success as a lecturer and, as well, a positive influence on many of my students who have become teachers (but not all of whom lecture).